Competitiveness of Indonesian Seaweed Exports to China and the United States - Andrian, Nur Andrian; Royhana, Imalatul; Afiani, Maya Afifah; Alamanda, Elok Fadhila (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2026)
Indonesia's seaweed sector has emerged as a strategic contributor to global aquaculture, though its export competitiveness varies across international markets. This study analyses dynamics of Indonesian seaweed exports to China and the United States from 2013 to 2023, focusing on comparative advantage, trade specialization, and intra-industry trade patterns. Utilizing secondary data from UN Comtrade (HS Code 1212), three quantitative indicators Revealed Comparative Advantage (RCA), Index of Trade Specialization (ISP), and Intra-Industry Trade (IIT) were employed to assess market performance and trade integration. The results indicate that Indonesia possesses a strong, consistent comparative advantage in the Chinese market, driven by stable demand for raw seaweed and carrageenan production, whereas competitiveness in the U.S. market has improved but remains more volatile. Positive ISP values indicate a high degree of export specialization, reflecting Indonesia's position as a net exporter of seaweed commodities in international markets. High and stable IIT values demonstrate robust intra-industry trade integration, underscoring Indonesia's active role in the global seaweed value chain beyond mere one-way commodity exports. Policy implications highlight the need to develop downstream processing, diversify products, enhance quality standards, and strengthen strategic trade partnerships to shift Indonesia's position from a raw material supplier to a value-added player in the global market, thereby ensuring sustainable export growth and long-term competitiveness.